A local-restart coupled strategy for simultaneous sizing and geometry truss optimization - Torii, André Jacomel; Lopez, Rafael Holdorf; Luersen, Marco Antônio (Latin American journal of solids and structures, 2011)
This paper presents an approach for the global optimization of truss sizing and geometry that is based on a probabilistic restart procedure coupled with a local search algorithm. The resulting algorithm is able to guarantee local optimality and provides a set of local optima which contain, with an increasing probability as the number of restarts increases, the global solution. The optimization problem searches for a truss structure of minimum volume, subject to stress constraints. The design variables are the bars cross-section areas and some nodal coordinates. Several loading conditions are also considered. Finally, four numerical examples are presented and the main aspects of the approach are discussed.